Оцінка індустріального навантаження та ступеня забрудненості атмосферного повітря Вінницької області - Шершун, О. М.; Колісник, А. В. (Київський національний університет імені Тараса Шевченка, 2017)
У роботі виконана оцінка індустріального навантаження у Вінницькій області за показниками кількості промислових об’єктів на одиницю площі та щільності викидів від них в атмосферу. На основі індексу забруднення оцінена ступінь забруднення атмосферного повітря у м. Вінниця.

The work describes the impact of economic activity on the atmospheric air of the Vinnytsia region; the estimation of industrial load was performed according to indicators such as the number of facilities per unit of territory and the density of atmospheric emissions; on the basis of the index of atmospheric pollution an assessment of the degree of air pollution in the city of Vinnitsa was completed. The atmospheric air of the Vinnytsia region is significantly affected by stationary sources of pollution. There are 338 potentially dangerous objects registered in the region. The largest number of them operates in the Vinnytsia region, and especially in the region center - Vinnytsia. The value of the industrial load index (the number of facilities per unit area) for the Vinnytsya region is six times higher than the average in the region - 0.012 facilities / km2. This area is the most loaded enterprises in the region. 48% of the objects are gas filling stations, functioning of which is a significant factor of anthropogenic influence on the state of atmospheric air quality. Most of the territory of the region has a low emission density (up to 1 ton / km2), while the highest value of this indicator is typical for Trostyanets district. In it the density of emissions into the air from stationary sources exceeds the average in the oblast (4.8 t / km2) almost 16 times. This also indicates that the Trostyanets district is allocated among other regions of Vinnytsya oblast a significant impact on the state of the air. This is explained by the fact that within the Trostyanets District, the Ladyzhin Thermal Power Plant (Ladyzhin) operates. It should be noted that according to the specific emissions from stationary sources of pollution of the region, the city of Ladyzhin take the first place. In the atmospheric air of Vinnytsia, stationary sources that operate in the oblast, emit only 11.7% of the total emissions of pollutants in the region. According to the results of the calculation of the air pollution index for the city of Vinnytsa air according to content of dust, sulfur dioxide, carbon monoxide, nitrogen dioxide, hydrogen fluoride, ammonia and formaldehyde corresponds to sanitary-hygienic requirements. The greatest influence on the city's atmospheric air is made by carbon monoxide, and the smallest is sulfur dioxide.
Estimation of industrial load and degree of air pollution in the Vinnytsia region
Keywords: атмосферне повітря; індустріальне навантаження; щільність викидів; забруднення атмосфери; atmospheric air; industrial load; emission density; atmospheric pollution